1997
DOI: 10.1002/he.9902
|View full text |Cite
|
Sign up to set email alerts
|

The American Doctorate and Dissertation: Six Developmental Stages

Abstract: Aspirations to advance knowledge led nineteenth-century American educators to create doctoral degrees and to found research universities. The original rationale for the doctorate was to teach graduate students who had an academic vocation how to conduct pure and applied research. The doctorate's 141-year-old degree requirements have remained substantially the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The award of a doctorate required successful attendance at seminars, submission of an acceptable thesis, and the passing of a comprehensive oral New Variant PhD in the UK 191 examination, and the emphasis was on original and creative research (Goodchild and Miller, 1997). Academic staff were invariably required to hold a PhD degree, engage in research and publish scholarly material.…”
Section: Genesismentioning
confidence: 99%
“…The award of a doctorate required successful attendance at seminars, submission of an acceptable thesis, and the passing of a comprehensive oral New Variant PhD in the UK 191 examination, and the emphasis was on original and creative research (Goodchild and Miller, 1997). Academic staff were invariably required to hold a PhD degree, engage in research and publish scholarly material.…”
Section: Genesismentioning
confidence: 99%
“…There are other practical reasons for symbolic citation connected with “bulking up” a dissertation or thesis; 80,000 to 100,000 words is now widely regarded as a standard length of a doctoral thesis in most parts of the West. However, the PhD thesis used to be more succinct and often published as a short book when first introduced to British higher education in the 1920s (Goodchild & Miller, 1997, p. 26). Hence, at a more mundane level, symbolic citation helps to pad out the thesis.…”
Section: Faking Qualitative Researchmentioning
confidence: 99%
“…These observations are not new. More than twenty years ago, writers like Noble (1994) and Goodchild and Miller (1997), observed that theses were being written in new ways and the formatting of academic thesis often deviated significantly from prescriptions offered by published guides and university handbooks (Swales & Najjar 1987, Partridge 2002.…”
Section: Introductionmentioning
confidence: 99%